Nilai Tambah Kopi Robusta (Studi Kasus Kelompok Tani Hutan Betara Bersatu Desa Bentenge Kecamatan Mallawa Kabupaten Maros) - Ayu Adelia; Arifin Arifin; Abd Asis Pata (Jurnal Agribis, 2026)
The objective of this study was to determine the value added generated from processing robusta coffee from green beans into coffee powder by the Betara Bersatu Forest Farmers Group in Bentenge Village, Mallawa District, Maros Regency. The research was conducted in Bentenge Village, Mallawa District, Maros Regency, for three months, from March to May 2025. Samples were selected using purposive sampling, deliberately choosing respondents deemed most knowledgeable about the coffee processing. The types and sources of data used were Primary Data and Secondary Data. The method employed was value-added analysis using the Hayami approach, based on primary data collected through questionnaires. The results indicate that processing robusta coffee from green beans into coffee powder provides significant value added. For the 100-gram and 200-gram packaging, the value-added ratio was 36.07%, while for the 500-gram packaging, the ratio was 20.09%. These figures are classified as moderate according to Hubeis (1997).